Clinical correlates of plasma brain-derived neurotrophic factor in post-traumatic stress disorder spectrum after a natural disaster. (30th October 2016) - Stratta, Paolo; Sanità, Patrizia; Bonanni, Roberto L.; de Cataldo, Stefano; Angelucci, Adriano; Rossi, Rodolfo; Origlia, Nicola; Domenici, Luciano; Carmassi, Claudia; Piccinni, Armando; Dell'Osso, Liliana; Rossi, Alessandro
Abstract: Clinical correlates of plasma Brain-Derived Neurotrophic Factor (BDNF) have been investigated in a clinical population with Post Traumatic Stress Disorder (PTSD) symptoms and healthy control subjects who survived to the L′Aquila 2009 earthquake. Twenty-six outpatients and 14 control subjects were recruited. Assessments included: Structured Clinical Interview for DSM-IV Axis-I disorders Patient Version, Trauma and Loss Spectrum-Self Report (TALS-SR) for post-traumatic spectrum symptoms. Thirteen patients were diagnosed as Full PTSD and 13 as Partial PTSD. The subjects with full-blown PTSD showed lower BDNF level than subjects with partial PTSD and controls. Different relationship patterns of BDNF with post-traumatic stress spectrum symptoms have been reported in the three samples. Our findings add more insight on the mechanisms regulating BDNF levels in response to stress and further proofs of the utility of the distinction of PTSD into full and partial categories. Highlights: Relationships of BDNF with PTSD symptoms of clinical and non-clinical samples hit by the same significant stress event. This is the first report on PTSD symptom correlates using a post-traumatic spectrum perspective. Along spectrum approach not only full, but partial or subthreshold PTSD also have been considered. The subjects with full-blown PTSD showed lower BDNF level than subjects with partial PTSD and controls. Different relationship patterns of BDNF with stress spectrum symptoms in full, partial PTSD and controls have been reported.